2017
DOI: 10.1111/rda.13042
|View full text |Cite
|
Sign up to set email alerts
|

The Comet assay for detection of DNA damage in canine sperm

Abstract: Sperm DNA integrity is a fundamental prerequisite in fertilization and embryo development. Among DNA integrity tests, the Comet assay is an accurate and sensitive test for the detection of sperm oxidative damage. The aim of this work was to evaluate sperm oxidative damage using the Comet assay and to study the correlation between Comet and routine assays for the evaluation of semen quality. Dogs were divided in two groups: group A (n = 6), comprising dogs with abnormal spermiogram, that is astheno-, terato- or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Dogs from different regions of the city of São Paulo, Brazil were used to evaluate the extent of DNA damage in the olfactory and respiratory epithelia, indicating increased DNA-damaging effects in relation to environmental factors [397]. Besides, the comet assay is also used for detection of DNA damage in canine sperm [398].…”
Section: Domestic Mammalsmentioning
confidence: 99%
“…Dogs from different regions of the city of São Paulo, Brazil were used to evaluate the extent of DNA damage in the olfactory and respiratory epithelia, indicating increased DNA-damaging effects in relation to environmental factors [397]. Besides, the comet assay is also used for detection of DNA damage in canine sperm [398].…”
Section: Domestic Mammalsmentioning
confidence: 99%
“…As the sperm head consists almost entirely of DNA, it has been hypothesized that sperm head morphometric parameters may reflect chromatin organization (Lange‐Consiglio et al., 2010). Studies have been carried out in dogs that relate DNA damage to sperm head morphometry (Núñez‐Martinez et al, 2005; Lange‐Consiglio et al., 2010; Urbano et al., 2017); but few studies evaluate the association between DNA damage and other routine sperm parameters (Pereira et al., 2017; Prinosilova et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently applied methodology for determining induction of DNA damage and repair processes in isolated cells is the alkaline SCGE, which can be used in a multiplicity of experimental models (Nikoloff et al 2014;Pereira et al 2017;Laborde et al 2020). For instance, Padula et al (2012) found increased DNA damage in CHO-K1 cells treated with 3.75 μg/mL AMZ for 16 h; Radakovic et al (2013) demonstrated that various AMZ concentrations (0.035, 0.35, 3.5, 35, and 350 μg/mL) induced DNA damage in human lymphocytes, finding the highest DNA damage with 3.5 μg/ mL while the highest concentrations of AMZ (35 and 350 μg/ mL) showed lower levels of DNA damage, they suggest that this is possibly due to formation of crosslinks.…”
Section: Discussionmentioning
confidence: 99%